Tissue- and Sex-Specific DNA Methylation Changes in Mice Perinatally Exposed to Lead (Pb) - Wang, Kai; Liu, Siyu; Svoboda, Laurie K.; Rygiel, Christine A.; Neier, Kari; Jones, Tamara R.; Colacino, Justin A.; Dolinoy, Dana C.; Sartor, Maureen A. (Frontiers in Genetics, 2020)
Lead (Pb) is a well-known toxicant that interferes with the development of a child’s nervous and metabolic systems and increases the risk of developing diseases later in life. Although studies have investigated epigenetic effects associated with Pb exposure, knowledge of genome-wide changes with in vivo low dose perinatal Pb exposure in multiple tissues is limited. Within the Toxicant Exposures and Responses by Genomic and Epigenomic Regulators of Transcription (TaRGET II) consortium, we utilized a mouse model to investigate tissue- and sex-specific DNA methylation. Dams were assigned to control or Pb-acetate water, respectively. Exposures started two weeks prior to mating and continued until weaning at post-natal day 21 (PND21). Liver and blood were collected from PND21 mice, and the DNA methylome was assessed using enhanced reduced representation bisulfite sequencing (ERRBS). We identified ~1000 perinatal Pb exposure related differentially methylated cytosines (DMCs) for each tissue- and sex-specific comparison, and hundreds of tissue- and sex-specific differentially methylated regions (DMRs). Several mouse imprinted genes were differentially methylated across both tissues in males and females. Overall, our findings demonstrate that perinatal Pb exposure can induce tissue- and sex-specific DNA methylation changes and provide information for future Pb studies in humans.